Taxometric Analysis of Secure Base Script Knowledge in Middle Childhood Reveals Categorical Latent Structure. Issue 3 (21st February 2019) - Waters, Theodore E.A.; Facompré, Christopher R.; Dujardin, Adinda; Van De Walle, Magali; Verhees, Martine; Bodner, Najda; Boldt, Lea J.; Bosmans, Guy
Abstract : Taxometric investigation of scripted attachment representations in lateadolescence and adulthood suggests that variations in secure base script knowledge consist of differences in degree (dimensional latent structure) rather than differences in kind (categorical latent structure). However, the latent structure of secure base script knowledge in younger cohorts has gone unexplored. This study presents a downward extension of prior taxometric work using the middle childhood version of the Attachment Script Assessment in a cross‐sectional sample of 639 normative‐risk children (age 8 to 13 years; M  =   10.77, SD  = 1.06). Results suggest that secure base script knowledge in middle childhood is categorically distributed. Taxometric curves revealed three distinct taxa, highlighting discontinuity in the latent structure of scripted attachment representations across development.